2022
DOI: 10.1177/14733250221124300
|View full text |Cite
|
Sign up to set email alerts
|

They would rather not have known and me kept my mouth shut’: The role of neutralisation in responding to the disclosure of childhood sexual abuse

Abstract: There is a well-established literature examining how perpetrators of child sexual abuse (CSA) neutralise the norms and beliefs that ordinarily prohibit such behaviours. However, there has been substantially less focus on how such techniques of neutralisation might also be applied by people and groups who were not directly involved in the abuse, who we might expect to be more supportive. Drawing on a thematic analysis of an open-ended survey (n=140) and semi-structured interviews (n=21) with adults who experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…More specifically, and related to positive bystander behavior, following the RAA it can be stated that the intention to perform positive bystander behaviors is determined by (A) the attitudes one has toward bystander behaviors, (B) the beliefs one has about whether relevant others approve of one engaging in bystander behavior (i.e., perceived norms), and (C) the beliefs one has about the fact that performing bystander behaviors is within their control or potential (i.e., perceived behavioral control) (Fishbein and Ajzen, 2010). Negative bystander attitudes, norms and perceived behavioral control, and a lack of knowledge, encompassing a culture of silence or tolerance for harassment and abuse (i.e., norms), lack of knowledge and understanding of what constitutes abuse, unawareness of reporting and supporting mechanisms, and fear of potential consequences are extensively described in the literature (Tillman et al, 2010;Banyard, 2011;McElvaney, 2019;Roberts et al, 2020;Cunnington and Clark, 2023) as factors that can explain the negative bystander behaviors (Tillman et al, 2010;Cunnington and Clark, 2023). All of this highlights the importance to improve and shift attitudes and norms, so that positive bystander behaviors are valued more and that it becomes the social norm (Verhelle et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, and related to positive bystander behavior, following the RAA it can be stated that the intention to perform positive bystander behaviors is determined by (A) the attitudes one has toward bystander behaviors, (B) the beliefs one has about whether relevant others approve of one engaging in bystander behavior (i.e., perceived norms), and (C) the beliefs one has about the fact that performing bystander behaviors is within their control or potential (i.e., perceived behavioral control) (Fishbein and Ajzen, 2010). Negative bystander attitudes, norms and perceived behavioral control, and a lack of knowledge, encompassing a culture of silence or tolerance for harassment and abuse (i.e., norms), lack of knowledge and understanding of what constitutes abuse, unawareness of reporting and supporting mechanisms, and fear of potential consequences are extensively described in the literature (Tillman et al, 2010;Banyard, 2011;McElvaney, 2019;Roberts et al, 2020;Cunnington and Clark, 2023) as factors that can explain the negative bystander behaviors (Tillman et al, 2010;Cunnington and Clark, 2023). All of this highlights the importance to improve and shift attitudes and norms, so that positive bystander behaviors are valued more and that it becomes the social norm (Verhelle et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of testimonials from (former) youth sport participants during the last decade have demonstrated similar outcomes in youth sport participants, underlining the high burden and many different adverse consequences (e.g., Fasting et al, 2002 ; Krug et al, 2002 ; Stafford et al, 2013 ; Mountjoy et al, 2016 ; Parent and Fortier, 2018 ; Wilinsky and McCabe, 2020 ; Parent et al, 2021 ; Schmidt et al, 2022 ). These negative outcomes are even greater when the child is of young age and when others do not intervene ( Tillman et al, 2010 ; Cunnington and Clark, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is often an aggressive act that frequently aims to express power and dominance over the victim. Sexual violence remains highly stigmatized in all settings, thus levels of disclosure of the assault vary making it difficult to estimate accurate prevalence rates (7)(8). In general, it is a widely underreported phenomenon, thus available data tend to underestimate the true scale of the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that children with intellectual and/or developmental disabilities are at a higher risk for sexual abuse than non-disabled peers (9)(10)(11)(12). A recent study demonstrated an overall prevalence of 31.7% of violence against children with disabilities and a two-fold increased risk of violence against disabled children compared to non-disabled peers (8). A systematic review and meta-analysis on the risk of violence against children with disabilities (11) reported a prevalence of 15% for sexual violence and OR 2.88 (2.24-3.69) for any disability based on nine studies and OR 4.62 (2.08-10.23) for mental or intellectual disability based on four studies.…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of testimonials from (former) youth sport participants during the last decade have demonstrated similar outcomes in youth sport participants, underlining the high burden and many different adverse consequences (e.g., Fasting et al, 2002;Krug et al, 2002;Stafford et al, 2013;Mountjoy et al, 2016;Parent and Fortier, 2018;Wilinsky and McCabe, 2020;Parent et al, 2021;Schmidt et al, 2022). These negative outcomes are even greater when the child is of young age and when others do not intervene (Tillman et al, 2010;Cunnington and Clark, 2023).…”
Section: Introductionmentioning
confidence: 99%